Leadership Style and Job Stress on Employee Performance through Job Satisfaction in BPJS Ketenagakerjaan in the Sulawesi Maluku Region - Dian Ayu Ismarani Basir; Achmad AC; Muchriady Muchran (Eduvest - Journal of Universal Studies, 2024)
This research aims to analyze the influence of leadership style and work stres on job satisfaction and employee performance, analyze the influence of job satisfaction on employee performance, and analyze the influence of leadership style and work stres on employee performance through job satisfaction at the BPJS Ketenagakeriaan Sulawesi Maluku Region. The data collection technique is through distributing questionnaires using data analysis techniques and analyzed with Amos. The results of the research show that leadership style has a significant positive effect on job satisfaction, work stres has a significant negative effect on job satisfaction, leadership style has a significant positive effect on employee performance, work stres has a negative and insignificant effect on job satisfaction, job satisfaction has a significant positive effect on employee performance . From the results of the Sobel test, it was found that job satisfaction can mediate the influence of leadership style and work stres on employee performance.